2000
DOI: 10.1007/bf03165877
|View full text |Cite
|
Sign up to set email alerts
|

Results of recent experiments with Pf-1000 facility equipped with new large electrodes

Abstract: The paper presents a modified PF-1000 megajoule plasma-focus (PF) facility operated at IPPLM in Warsaw. In order to study PF discharges at higher discharge current, several diagnostics tools have been developed and tested. The preliminary studies of current sheath dynamics, and measurements of the discharge currents, X-ray, fast ion, and neutron emission at higher energy levels, are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Numerous experiments have shown that when the current reaches the magnitude of millions of amperes, it can generate a significant axial magnetic pressure that constrains the plasma to accelerate inward and collide (Klir et al, 2020;Kubes et al, 2020). The axial acceleration and radial compression phases have been relatively accurately described through a two-dimensional MHD model (Scholz et al, 2000). The current intensity on the surface of the Sun is much higher than in the laboratory, reaching 10 13 amperes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Numerous experiments have shown that when the current reaches the magnitude of millions of amperes, it can generate a significant axial magnetic pressure that constrains the plasma to accelerate inward and collide (Klir et al, 2020;Kubes et al, 2020). The axial acceleration and radial compression phases have been relatively accurately described through a two-dimensional MHD model (Scholz et al, 2000). The current intensity on the surface of the Sun is much higher than in the laboratory, reaching 10 13 amperes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…All discharges in the PF-1000U facility were investigated by means of routine diagnostics, i.e. by recording voltage and current-derivative waveforms, laser-interferometer images (from a multi-frame Mach-Zehnder system which was operated with 1 ns Nd : YLF laser pulses of wavelength λ = 527 nm, and a spatial resolution of about 500 μm), hard x-ray and neutron-induced signals (obtained from standard scintillation probes), as well as fusion-neutron yields (measured with silver-activation counters), etc [17][18][19].…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Detailed studies of micro-structures of a PF pinch column have been performed in a few cases only [10,15,16]. Some attention to this question was paid during the extensive experimental studies, performed with the mega-joule PF-1000 facility at IPPLM in Warsaw, Poland, over several years [17][18][19]. This device, which is so far the largest Mather-type machine in the world, was modernized to become the PF-1000U facility about 2 years ago.…”
Section: Introductionmentioning
confidence: 99%